Meniscal Tear in Knees Without Surgery and the Development of Radiographic Osteoarthritis Among Middle-Aged and Elderly Persons: The Multicenter Osteoarthritis Study - Englund, Martin (2009)
OBJECTIVE: Although partial meniscectomy is a risk factor for the development of knee osteoarthritis (OA), there is a lack of evidence that meniscal damage that is not treated with surgery would also lead to OA, suggesting that surgery itself may cause joint damage. Furthermore, meniscal damage is common. The aim of this study was to evaluate the association between meniscal damage in knees without surgery and the development of radiographic tibiofemoral OA. METHODS: We conducted a prospective case–control study nested within the observational Multicenter Osteoarthritis Study, which included a sample of men and women ages 50–79 years at high risk of knee OA who were recruited from the community. Patients who had no baseline radiographic knee OA but in whom tibiofemoral OA developed during the 30-month followup period were cases (n = 121). Control subjects (n = 294) were drawn randomly from the same source population as cases but had no knee OA after 30 months of followup. Individuals whose knees had previously undergone surgery were excluded. Meniscal damage was defined as the presence of any medial or lateral meniscal tearing, maceration, or destruction. RESULTS: Meniscal damage at baseline was more common in case knees than in control knees (54% versus 18%; P < 0.001). The model comparing any meniscal damage with no meniscal damage (adjusted for baseline age, sex, body mass index, physical activity, and mechanical knee alignment) yielded an odds ratio of 5.7 (95% confidence interval 3.4–9.4). CONCLUSION: In knees without surgery, meniscal damage is a potent risk factor for the development of radiographic OA. These results highlight the need for better understanding, prevention, and treatment of meniscal damage.